Incidence Of Gingivitis Related To Smoking Habits In Adult Males In Makassar City - Ramli, Rachmat; Nurhaedah, Nurhaedah; Rahmat, Rezqiqah Aulia (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Damage tooth is a condition where somebody experience disturbance good on pattern development teeth, pattern eruption and also on integrity its structure. Disturbance the can in the form of excessive plaque, caries​ on crown and root teeth, halitosis, changes color teeth, wrong One habit bad that can cause damage tooth is smoking. This is can to elevate the occurrence success bad mouth, Purpose​ Study is for know description habit smoke to gingivitis incidence in man mature age 36 - 45 years in Nusa Harapan complex the beauty of Makassar City. Method study this use type study descriptive through approach observational with researching and inspect direct condition health tooth and mouth on community in the Nusa Harapan Complex the beauty of Makassar City. Data collection with results collected records​ direct by researcher with intra oral examination of sign clinical gingivitis and interview by every respondents. Results study that habit smoke with gingivitis incidence in man adults in the complex Comp. The Land of Hope beautiful Makassar with the number of samples is 42 people. The occurrence of gingivitis in smoker man adults in the Nusa Harapan Complex the beauty of Makassar City was found with category light as much as 59.5%. Conclusion that gingivitis incidence based on smoking duration , where part big subject study experiencing mild gingivitis with a duration of smoking 1 – 10 years by 26.2%, and based on amount the most cigarettes smoked per day​ found subject study on smoker 11 – 20 cigarettes / day with mild gingivitis as much as 33.3%.